An Analysis of Feminization of Agriculture in Bihar: Dimension and Trend - Jaiswal, Amrit Lal; Kumar, Rajesh (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Over the past two decades, women’s participation in agriculture in Bihar has increased significantly, surpassing that of men. This study investigates the various dimensions and factors contributing to this shift. Bihar is predominantly an agrarian state, with approximately 70 percent of its population residing in rural areas and primarily dependent on agriculture. However, in recent decades, factors such as mechanization, climate change, and specific market conditions have prompted men to disengage from agricultural work in many countries. Farming is no longer perceived as a lucrative occupation, leading to migration to nonagricultural sectors. Additionally, a substantial portion of the male population has migrated to urban areas in pursuit of livelihood opportunities. Consequently, women have remained in the villages and have assumed agricultural responsibilities alongside their household duties. This transition has resulted in an increase in women’s participation in agriculture in Bihar, a phenomenon referred to as the feminization of agriculture. In this study, we explore the trends and dimensions of this feminization, examine how women’s growing role in agriculture is influencing Bihar’s agricultural sector, and explore what policies could be implemented to ensure that this transformation contributes positively to agricultural development.